The life cycle of the common octopus : a novel - Knight, Emma (Emma L.) ([New York] : Pamela Dorman Books/Viking, 2025)
Arriving at the University of Edinburgh for her first term, Pen knows her divorced parents back in Canada are hiding something from her. She believes she$1 (Bll find the answer here in Scotland, where an old friend of her father$1 (Bs$1 (Bnow a famous writer known as Lord Lennox$1 (Blives. When she is invited to spend the weekend at Lord Lennox$1 (Bs centuries-old estate with his enveloping, fascinating family, Pen begins to unravel her parents$1 (Bsecret, just as she$1 (Bs falling in love for the first time . . . As Pen experiences the sharp shock of adulthood, she comes to rely on herself for the first time in her life.s
Keywords: College students -- Fiction; Family secrets -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Scotland -- Fiction